1989
DOI: 10.1149/1.2096748
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Approach to Accurately Model Shallow B and  BF 2 Implants in Silicon

Abstract: In this paper, an improved modeling approach is described for simulating as-implanted boron impurity profiles for B + and BF2 ~ implants into single*crystal silicon. This method uses the sum of two Pearson distribution functions to account for the nonchanneling and channeling components of the implant distribution. The ratio of the two Pearson functions varies with dose, which accounts for the change in the degree of channeling with dose. This modeling approach has been compared with experimentally measured SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…The "channeled" fraction forms a long-range edge of a profile (z > 250 nm) due to the ions captured into the stable channeling at the crystal surface. For these fractions, the shapes of partial doping profiles are qualitatively similar to those of the asymmetric Pearson type IV distributions that are generally accepted in the physics of implantation and are used as basis functions w r,ch of the standard "dual Pearson" model [20].…”
Section: Problem Setupmentioning
confidence: 89%
See 2 more Smart Citations
“…The "channeled" fraction forms a long-range edge of a profile (z > 250 nm) due to the ions captured into the stable channeling at the crystal surface. For these fractions, the shapes of partial doping profiles are qualitatively similar to those of the asymmetric Pearson type IV distributions that are generally accepted in the physics of implantation and are used as basis functions w r,ch of the standard "dual Pearson" model [20].…”
Section: Problem Setupmentioning
confidence: 89%
“…Legendre [18]) polynomials, the heuristic empirical models [19][20][21] are widely used for practical calculations. To some degree, they reflect the physics of ion transport and implantation into crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to a multiday BCA simulation using a large number of ion trajectories, values of the simulated aluminum concentration do not monotonically decrease when the aluminum concentration becomes comparable to an n-type drift-layerdoping level (in the order of 10 15 cm -3 ). A continuous-function approximation, just like the dual-Pearson approach established for ion implantation into silicon (Tasch et al, 1989), is thus needed. The historic development and basic concepts of boron diffusion in SiC are reviewed as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the simulation depends on the function used. Functions to express ion implantation profiles have also been developed by using Gauss, joined half Gauss [1], Pearson [2,3], dual Pearson [4,5], and tail functions [6][7][8][9]. It has been demonstrated that the dual Pearson accurately covers the whole ion implantation profile, and it is the standard function implemented in commercial simulators [10].…”
Section: Introductionmentioning
confidence: 99%